2018
DOI: 10.1108/ijwhm-10-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

Stand Up to Work: assessing the health impact of adjustable workstations

Abstract: Purpose Sedentary behavior is linked to health risks, and prolonged sitting is prevalent among office workers. Adjustable workstations (AWS) promote health by allowing transitions between sitting and standing. Stand Up to Work compares workers with AWS to traditional desks (TD). The paper aims to discuss these issues. Design/methodology/approach Employees were randomly selected from one office floor to receive AWS, two identical floors maintained TD. Participants received workplace wellness and ergonomic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This seems to also resonate with the goal of active design, which is to encourage physical activity at home as explained in the literature [26]. Again, this may provide support to the submission of previous authors that the distance required to reach key destinations in residential buildings such as bed rooms, living rooms, kitchen, washrooms and others could affect occupants' sedentary lifestyle [24,25].…”
Section: Sedentary Behaviour and Physical Activity Among The Residents In Different Housing Typessupporting
confidence: 73%
See 1 more Smart Citation
“…This seems to also resonate with the goal of active design, which is to encourage physical activity at home as explained in the literature [26]. Again, this may provide support to the submission of previous authors that the distance required to reach key destinations in residential buildings such as bed rooms, living rooms, kitchen, washrooms and others could affect occupants' sedentary lifestyle [24,25].…”
Section: Sedentary Behaviour and Physical Activity Among The Residents In Different Housing Typessupporting
confidence: 73%
“…Active design impacts on human health by helping building occupants integrate regular physical activity into their daily life unconsciously [22,23]. Based on the principles of active design, it seems feasible that layout of homes and, in particular, the distance required to reach key destinations in residential buildings such as bed rooms, living rooms, kitchens, washrooms and others could affect both occupants' levels of movement and time spent sitting or lying [24,25]. For example, the Center for Active Design [26] had noted that having staircase, appealing, supportive walking routes such as lobbies and corridors and location of functions within buildings to encourage walking can promote physical activity and the health of occupants.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies were also rated as ‘high’ RoB due to deviations from intended interventions (data not analysed according to intention-to-treat principles 40 58 74 79 ) and missing outcome data. 76 79 83 87 An unclear risk level was typically assigned based on inadequate reporting of randomisation (k=12), concerns with missing outcome data (k=11) and/or bias in measurement of the outcome (k=9). Low risk was still permitted with lack of blinding, given the context (behavioural intervention) in which allocation is impossible to conceal from participants and is generally known to staff, and in which outcomes are collected objectively.…”
Section: Resultsmentioning
confidence: 99%
“…In general, because of the naturalistic settings in which these studies took place, the overall risk of bias among individual studies was moderate (see Table 4). Despite the use of cluster randomisation techniques and allocation blinding, baseline imbalances were a high source of bias in five studies [45,59,62,63,78]. Contamination during the intervention due to spillover effects may have biased findings in six studies [63,67,68 four interventions that increased fat-free mass/total lean mass [45,64,67,75], one intervention that reduced body fat percentage [67], and one intervention that reduced total fat mass [75].…”
Section: Risk Of Bias For Individual Studies Is Presented Inmentioning
confidence: 99%
“…53,58,[61][62][63]69,74,78] did not result in improvements in cardiometabolic risk markers.3.4.4 Active controlsOf the ten active control conditions[46,47,[50][51][52][53][54]58,63,77], none reported any improvement in cardiometabolic risk markers; however, Healy et al[51] found that the (active) control group experienced a significant worsening of clustered cardiometabolic risk scores, fasting glucose levels, and HOMA2-%S levels compared to baseline.3.5 Sedentary behaviour outcomesOf the 20 interventions which showed an improvement in at least one cardiometabolic risk marker[45,50-52,54,59,62,64-68,70-73,75-77,79], fifteen (75%) also reported significantly reducing (p < 0.05) sedentary behaviour [45,50-52,54,59,62,64-68,71-73]. The remaining five did not report on sedentary behaviour change.…”
mentioning
confidence: 99%